Resting energy expenditure can be assessed by fat-free mass in female athletes regardless of body size - Taguchi, M.; Ishikawa-Takata, K.; Tatsuta, W.; Katsuragi, C.; Usui, C.; Sakamoto, S.; Higuchi, M. (Journal of Nutritional Science and Vitaminology, 2011)
Energy requirements can be estimated from resting energy expenditure (REE). However, little is known about factors influencing REE in Japanese female athletes. This study was performed to evaluate the relationship between REE and body composition in Japanese female athletes with a wide range of body sizes. Ninety-three athletes (age 20.3±1.2 y, height 162.8±6.4 cm, body weight (BW) 57.0±9.2 kg, fat-free mass (FFM) 45.4±6.2 kg) were classified into three groups according to BW: small-size (S) (n=34), medium-size (M) (n=34), and large-size (L) (n=25). Systemic and regional body compositions (skeletal muscle (SM), fat mass (FM), bone mass (BM), and residual mass (RM)) were estimated by dual energy X-ray absorptiometry (DXA). Measured resting energy expenditure (REEm) was evaluated by indirect calorimetry. Marked differences were found in REEm (S: 1,111±150, M: 1,242±133, L: 1,478±138 kcal/d), and systemic and regional body compositions among the three groups. REEm was strongly correlated with FFM, and absolute values of RM and SM increased significantly according to body size. There was good agreement between REEm and estimated REE (REEe) from the specific metabolic rates of four major organ tissue level compartments. These data indicate that REE for female athletes can be attributed to changes in organ tissue mass, and not changes in organ tissue metabolic rate. That is, change in REE can be explained mainly by the change in FFM, and REE can be assessed by FFM in female athletes regardless of body size.